Role and potential therapeutic value of histone methyltransferases in drug resistance mechanisms in lung cancer - Zhang, Linxiang; Zhang, Xueying; Shi, Yan; Ni, Yuhan; Fei, Jiaojiao; Jin, Zhixin; Li, Wenjuan; Wang, Xiaojing; Wu, Nan (Frontiers in Oncology, 2024)
Lung cancer, ranking second globally in both incidence and high mortality among common malignant tumors, presents a significant challenge with frequent occurrences of drug resistance despite the continuous emergence of novel therapeutic agents. This exacerbates disease progression, tumor recurrence, and ultimately leads to poor prognosis. Beyond acquired resistance due to genetic mutations, mounting evidence suggests a critical role of epigenetic mechanisms in this process. Numerous studies have indicated abnormal expression of Histone Methyltransferases (HMTs) in lung cancer, with the abnormal activation of certain HMTs closely linked to drug resistance. HMTs mediate drug tolerance in lung cancer through pathways involving alterations in cellular metabolism, upregulation of cancer stem cell-related genes, promotion of epithelial-mesenchymal transition, and enhanced migratory capabilities. The use of HMT inhibitors also opens new avenues for lung cancer treatment, and targeting HMTs may contribute to reversing drug resistance. This comprehensive review delves into the pivotal roles and molecular mechanisms of HMTs in drug resistance in lung cancer, offering a fresh perspective on therapeutic strategies. By thoroughly examining treatment approaches, it provides new insights into understanding drug resistance in lung cancer, supporting personalized treatment, fostering drug development, and propelling lung cancer therapy into novel territories.